2023
DOI: 10.1007/s11356-023-26899-1
|View full text |Cite
|
Sign up to set email alerts
|

3,4-Dioxygenated xanthones as antifouling additives for marine coatings: in silico studies, seawater solubility, degradability, leaching, and antifouling performance

Abstract: Marine biofouling pollution is a process that impacts ecosystems and the global economy. On the other hand, traditional antifouling (AF) marine coatings release persistent and toxic biocides that accumulate in sediments and aquatic organisms. To understand the putative impact on marine ecosystems of recently described and patented AF xanthones (xanthones 1 and 2), able to inhibit mussel settlement without acting as biocides, several in silico environmental fate predictions (bioaccumulation, biodegradation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Nevertheless, it was found that, after 45 days of the leaching assays, xanthones 97 and 98 were leached from the PDMS-based marine coatings by approximately 17% and 25%, respectively, whereas the same compounds showed a leaching value lower than 2% from the PU-based coatings, as reported in subsection 3.2. These results may indicate a possible short time effect of these compounds in the PDMS coating [79].…”
Section: Silicone-based Coatingsmentioning
confidence: 77%
See 3 more Smart Citations
“…Nevertheless, it was found that, after 45 days of the leaching assays, xanthones 97 and 98 were leached from the PDMS-based marine coatings by approximately 17% and 25%, respectively, whereas the same compounds showed a leaching value lower than 2% from the PU-based coatings, as reported in subsection 3.2. These results may indicate a possible short time effect of these compounds in the PDMS coating [79].…”
Section: Silicone-based Coatingsmentioning
confidence: 77%
“…and the evaluation of the anti-settlement activity against mussel M. galloprovincialis. The PU marine coating containing xanthone 97 was shown to be more effective against the settlement of the mussel larvae after 40 hours of incubation (10% larval settlement) than the control PU marine coating (35% larval settlement) [79]. As expected from the low water solubility, xanthone 97 presented a leaching value lower than 2%, after 45 days in artificial seawater, indicating the potential to generate long-lasting PU-based coatings.…”
Section: Polyurethane-based Coatingsmentioning
confidence: 85%
See 2 more Smart Citations
“…Over the past decade, various AF agents have been developed, such as copper and copper compounds, zinc, Irgarol 1051 and Sea-Nine 211, since the use of triphenyltin (TBT) system AF coatings have been banned in the worldwide due to their environmental toxicity [ 6 , 7 , 8 ]. However, the release of metals from copper- and zinc-based AF coatings are also deleterious to marine organisms which are widely used in the industry [ 9 , 10 , 11 , 12 ]. Therefore, based on the adverse effects of excessive release of metal ions in the widely used AF coatings on the development of marine ecosystems, it is of great significance to develop environmentally friendly coatings with nontoxic AF agents.…”
Section: Introductionmentioning
confidence: 99%